Niespójność Pawłowego wywodu w Rz 2,1-29? Odpowiedź na tezę Eda Parisha Sandersa - Rakocy, Waldemar (The Biblical Annals, 2015)
In reply to Ed P. Sanders’s thesis we state that Romans 2 does not show inconsistencies within itself, neither with the immediate context, nor with other places in the Epistle. We prove it mainly by analyzing formal subjects in the text. Inconsistencies in Romans 2 were the main reason leading Sanders to the conclusion that chapter 2 derives from the homiletical material of Diaspora Judaism (a synagogue sermon). We don’t rule out this possibility altogether but we point out that his arguments supporting the hypothesis are not sufficient and require additional proofs.